Fetal and Perinatal Brain Autopsy: Useful Macroscopic Techniques Including Agar In-situ and Pre-Embedding Methods. (August 2021) - van Dijk, Marcory CRF; Kornegoor, Robert; Mol, Suzanne; Rodriguez, Michael
Fragile perinatal and fetal brains are the rule rather than the exception for developmental neuropathologists. Retrieving the fresh brain from the skull and examining early fetal, macerated or severely hydrocephalic brains after fixation can be a challenge. Textbooks on neurodevelopmental pathology mention these challenges to macroscopic examination of the developing central nervous system only in passing, but many perinatal pathologists recognize this diagnostic problem. We reviewed protocols and publications on the removal, fixation, slicing and sampling of these fetal- and perinatal brains. In addition, we describe a technique to facilitate the removal of severely hydrocephalic brains with very thin cerebral walls from the skull by replacing the intraventricular fluid with agar in-situ . Furthermore, we present a method for post-fixation pre-embedding in agar to facilitate slicing, macroscopic examination and sampling of fragile and macerated brains.